Time and progress: Conceptual History and Cartesian modernity - Quintela González, Héctor (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2024)
This paper attempts to evaluate the relevance of the work of René Descartes (1596-1650) in the genesis and unfolding of Modernity from the theoretical framework provided by the Conceptual History (Begriffsgeschichte) developed by Reinhart Koselleck. In particular, special attention is paid to the temporal dimension contained in Koselleck's Conceptual History and the role played by Descartes in the constitution of the modern concept of progress, which, according to Koselleck, summarises the experience of a new epoch in one word. The aim is to shed new light on a commonplace in the history of philosophy: the attribution of the paternity of the modern epoch to Descartes.
Keywords: Descartes; Conceptual History; Modernity; progress; time